French Ambulatory Cesarean: Mother and Newborn Safety. Issue 1 (24th March 2021) - Dimassi, K.; Ami, O.; Fauck, D.; Simon, B.; Velemir, L.; Triki, A.
Abstract : ( Int J Gynecol Obstet . 2020;148:198–204) Cesarean delivery involves a longer length of hospital stay, higher rates of morbidity, and greater costs and need for care compared with vaginal delivery. Misgav Ladach cesarean (MLC) is a widely used cesarean procedure, though it may impede future fertility. French Ambulatory Cesarean Section (FAUCS) appears to shorten recovery time. This study aimed to assess the results of FAUCS for maternal and neonatal safety in a unit that introduced FAUCS in January 2018.